Penerapan Akuntansi Pada Usaha Peternakan Ayam Potong (Studi Kasus Usaha Mitra PT. Mustika Peternakan Ayam Di Kecamatan Gayam) - Devita Sari; Hermawan Budi Prasetiyo; Hasan Bisri (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2022)
There are many business competitors vying for their business to run well. One of them is a chicken farm business, many people have the desire to have a business in the field of animal husbandry. The thing that prompted the author to investigate further is whether the accounting records of beef chickens in Gayam District have been carried out property or not. From the description above, the formulation of the problemis how to apply accounting to a chicken farm business in Gayam District. This research uses qualitative research methods. In qualitative research, the instrument is a person or public relations instrument, namely the researcher himself. To be able to become an instrument, the researcher must have broad theoretical and insightful provisions so that he is able to ask questions, analyze, take pictures, ans construct the social situations under study. Clear and meaningfully. Based on the discussion, it can be concluded that, the owner of the broiler farm does not fully understand the application of accounting. There are no financial reports on the broiler farm, and have not been able to prepare financial statements based on the application of accounting.